Professor Zbigniew Dąbrowski’s Anniversary - Grzegorz KLEKOT (Archives of Acoustics)
Seventieth anniversary of Professor Engineer Zbigniew Dąbrowski - key figure in Polish vibroacoustics. Professor Dąbrowski is an outstanding Polish scientist in the disciplines of mechanics and machine construction and exploitation. He has established an original scientific school of solving non-linear problems in machine construction and diagnostics. In 2009–2015 he presided the Section of Vibroacoustics of Accoustics Committee at Polish Academy of Sciences. Currently he is the president of the Section of Architecture, Environment Protection and Vibroacoustics of the same Committee.